1991
DOI: 10.1007/bf00361340
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic distribution of region-specific maternal protein during oogenesis and early embryogenesis of Xenopus laevis

Abstract: For analysing spatial distribution of maternal proteins in an amphibian egg, monoclonal antibodies specific to certain regions were raised. One monoclonal antibody was found (MoAB Xa5B6) which reacted specifically with the animal hemisphere of the mature Xenopus laevis egg. The maternal protein that reacted with the MoAb Xa5B6 was shown to be distributed asymmetrically along the dorso-ventral axis in the upper region of the equatorial zone of the fertilized egg. At late blastula stage, the antigen protein coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…1 B, insert, arrows). It was reported that the radial striations were disorganized and that the antigen molecules were uniformly distributed all over the animal hemisphere of the mature oocyte in the oviduct (Suzuki et al 1991). In the present experiment, progesterone-treated oocytes underwent germinal vesicle breakdown in vitro after 6 h. During progesterone-induced maturation (Fig.…”
Section: Effects Of Germinal Vesicle Removal and K+-free Solutionmentioning
confidence: 62%
See 2 more Smart Citations
“…1 B, insert, arrows). It was reported that the radial striations were disorganized and that the antigen molecules were uniformly distributed all over the animal hemisphere of the mature oocyte in the oviduct (Suzuki et al 1991). In the present experiment, progesterone-treated oocytes underwent germinal vesicle breakdown in vitro after 6 h. During progesterone-induced maturation (Fig.…”
Section: Effects Of Germinal Vesicle Removal and K+-free Solutionmentioning
confidence: 62%
“…Production of the hybridoma, preparation of the monoclonal antibody (MoAb Xa5B6) and the procedures for immunohistochemical examination were described in ore previous paper (Suzuki et al 1991).…”
Section: Preparation Of Moab Za5b6 and Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Production of the hybridomas † , preparation of the monoclonal antibody, and the procedures for immunohistochemical analysis have been described in Suzuki et al (1991).…”
Section: Methodsmentioning
confidence: 99%